Mitigating Student Late Attendance at SMK Nasional Malang: Exploring the Guidance and Counseling Services - Putri, Destya Indah Maharani; Ersandy, Navilla Rahma; Qadah, Ta Sa Dzul; Flurentin, Elia; Dewi, Nurma Septiyana; Hanafi, Husni (Universitas Negeri Malang, 2024)
Being late is a bad habit to attend after the specified time. This habit is a form of student indiscipline at school. All students should have a disciplined attitude, but in reality, there are still many students who are late every day. In general, this research aims to identify and evaluate the forms and conditions (1) Patterns of student late attendance, (2) Background factors, (3) Counselor handling of late students, (4) Counselor perceptions of late students, (5) Results of counselor handling that occur in SMK Nasional, Malang. The method used in this research is descriptive, and the form of research is survey research. The subjects in this research were six students and four guidance and counseling teachers. This research uses observation, interview, and documentation data collection techniques. The research results showed that six students were often late and were given treatment in the form of behavior contracts and counseling by the guidance counselor. Three students experienced a decrease in late behavior, while the other three students had been discipline in their attendance. Keywords: guidance and counseling; late attendance; behavior contract; students indiscipline